1993
DOI: 10.1128/aem.59.9.2771-2776.1993
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic characterization of copper-resistant mutants of Methylosinus trichosporium OB3b

Abstract: Cultures of Methylosinus trichosporium OB3b grown in the presence of very low concentrations of copper synthesize a soluble methane monooxygenase (sMMO) that efficiently catalyzes the oxidation of trichloroethylene and other organic pollutants. Recently, we isolated five M. trichosporium OB3b mutants that express sMMO activity when grown in the presence of elevated copper concentrations (P. A. Phelps, S. K. Agarwal,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
52
0
1

Year Published

1994
1994
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(57 citation statements)
references
References 28 publications
4
52
0
1
Order By: Relevance
“…Methanotrophs clearly respond to copper, and as such, these microbes must have some mechanism to sense and collect copper from the environment. Initial evidence for such machinery came from the characterization of constitutive sMMO mutants (sMMO C ) of Methylosinus trichosporium OB3b constructed using random chemical mutagenesis (56,57). These mutants had impaired copper uptake compared to the M. trichosporium OB3b wild type, suggesting that methanotrophs can synthesize a copper-complexing agent, or chalkophore ("chalko" is Greek for "copper").…”
mentioning
confidence: 99%
“…Methanotrophs clearly respond to copper, and as such, these microbes must have some mechanism to sense and collect copper from the environment. Initial evidence for such machinery came from the characterization of constitutive sMMO mutants (sMMO C ) of Methylosinus trichosporium OB3b constructed using random chemical mutagenesis (56,57). These mutants had impaired copper uptake compared to the M. trichosporium OB3b wild type, suggesting that methanotrophs can synthesize a copper-complexing agent, or chalkophore ("chalko" is Greek for "copper").…”
mentioning
confidence: 99%
“…This limits the speed with which sMMOcontaining biomass can be generated. In addition, transcription of the smnino locus is repressed by low concentrations of copper ions (0.25 ,uM) (47); hence, sMMO may not be expressed in the natural environment, and it will be difficult to use M. trichosporilum OB3b for in situ bioremediation (6,12,39). Furthermore, sMMO is competitively inhibited by the substrates methane and TCE (35).…”
mentioning
confidence: 99%
“…While the crystal structure of Methylococcus can be found on this subject (Cooksey, 1993;Reusing and Grass, 2003;Lu et al, 2003;Harrison et al, 2000;Nies, 1999;Vulpe and Packman, 1995;Puig et al, 2002); therefore, no further details will be discussed in this literature review. In contrast to most other microorganisms, copper plays a very important role in methanotroph physiology; however, it is believed they are not typically starved for copper in the environment (Berson and Lidstrom, 1996;Fitch et al, 1993). Despite this, it has been suggested by numerous researchers that these organisms may possess a specific copper-trafficking system due to their high copper dependencies.…”
Section: Methanotrophic Bacteriamentioning
confidence: 99%
“…To better understand the physiological role and ecological significance of copper regulation in methanotrophic M. trichosporium OB3b, Fitch et al (1993) used five previously isolated mutants (Phelps, et al, 1992) that exhibited constitutive sMMO activity in the presence of copper; an activity that would normally be repressed in wild-types. It was suggested that the lack of effects on growth rate and sMMO expression due to copper in these mutants was not a result of increased stability of sMMO to copper deactivation.…”
Section: Chronological Characterization Of Methanobactinmentioning
confidence: 99%